GAMBARAN KECEMASAN DALAM MENJALIN HUBUNGAN PADA PEREMPUAN DEWASA AWAL YANG MENGALAMI FATHERLESS - Ni Wayan Intan Windusari; Rai Hardika; Diah Widiawati Retnoningtias (Universitas Mercu Buana, 2026)
This study aims to describe relationship anxiety in young adult women who have been orphaned. The research approach used was a qualitative case study method, involving five informants aged 18–25 years. The results showed that the anxiety experienced by participants was reflected in three main aspects: physical aspects, including heart palpitations, trembling, and difficulty sleeping when facing conflict or communicating. Cognitive aspects include overthinking, resentment towards partners, and negative beliefs about relationships. And behavioral aspects include impulsive reactions, emotional dependence, and dominant or avoidant behavior in relationships. Of these three aspects, the behavioral aspect was found to be the most dominant, seen from consistent behavioral patterns such as the tendency to maintain unhealthy relationships, fear of abandonment, and showing excessive control in relationships. These findings confirm that the experience of orphanhood has a strong impact on the expression of anxious behavior in romantic relationships in young adult women.